2015
DOI: 10.1007/s10780-015-9240-z
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Challenges of Technology in High Schools: A Voice from Educational Leaders with a Freire Echo

Abstract: The purpose of this study is to document the perceptions of school leaders pertaining to the benefits and challenges of technology in high schools located on Prince Edward Island (PEI) (Canada). For this qualitative study, we interviewed 11 educational leaders representing the PEI Department of Education, principals, vice-principals, and department heads. Most participants indicated that technology activated reverse mentorship among teachers and students, and technology positively affected student motivation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Accordingly, current developments suggest that several countries are starting to include digital competencies in their respective curricula (e.g., Siddiq et al, 2016;Flórez et al, 2017). The advantages of using technology in classrooms, such as facilitating learning processes (Shute and Rahimi, 2017), motivating students (Saine, 2012) or preparing youths for the digital requirements of their future career (Preston et al, 2015) have been suggested by several studies. However, the rapid transition to distance teaching has caught many schools unprepared (Helm et al, 2021).…”
Section: Conversion To Distance Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, current developments suggest that several countries are starting to include digital competencies in their respective curricula (e.g., Siddiq et al, 2016;Flórez et al, 2017). The advantages of using technology in classrooms, such as facilitating learning processes (Shute and Rahimi, 2017), motivating students (Saine, 2012) or preparing youths for the digital requirements of their future career (Preston et al, 2015) have been suggested by several studies. However, the rapid transition to distance teaching has caught many schools unprepared (Helm et al, 2021).…”
Section: Conversion To Distance Teachingmentioning
confidence: 99%
“…Mixed forms of in-person and distance teaching, such as the use of self-produced explanatory videos for independent familiarization with new learning content, soon became increasingly important (Klieme, 2020.). As more evidence of the many possibilities of digital teaching became available (e.g., Saine, 2012;Preston et al, 2015;Chauhan, 2017;Shute and Rahimi, 2017), elementary school teachers had to become familiar with these teaching techniques and learning methods. However, the use of digital teaching methods was often contraindicated in elementary schools since there was a risk of overtaxing the students (e.g., .…”
Section: Teachers' Digital Equipment and Skillsmentioning
confidence: 99%
“…La sociedad actual se ha configurado de tal forma que las tecnologías de la información y la comunicación (TIC) ocupan un lugar fundamental (Preston et al, 2015). Sin tener verdadera consciencia de ello, diariamente acudimos a los dispositivos tecnológicos para realizar las tareas más cotidianas.…”
Section: Introductionunclassified
“…Mobile phones have been found to be a powerful tool to support student-centred and directed learning opportunities (Preston et al, 2015) when used to record lectures, instructions for assignments, or to photograph experimental or fieldwork. Another constructive use is for student collaboration (Corbeil & Valdes-Corbeil, 2007), which is necessary for the successful implementation of active learning.…”
Section: Mobile Technologies -What the Literature Showsmentioning
confidence: 99%